User experiences of virtual reality technologies for healthcare in learning: an integrative review. Issue 1 (2nd January 2022) - Mäkinen, Henna; Haavisto, Elina; Havola, Sara; Koivisto, Jaana-Maija
ABSTRACT: The aim of this integrative review was to analyse the usage of different virtual reality (VR) technologies in learning and user experiences (UXs) of these technologies in healthcare practice and education. The integrative review was conducted in spring 2019 by searching eight international databases. The searches retrieved n  = 26 original articles that were quality checked and included for the review. Three different VR technologies used in the field of healthcare education and practice were identified: haptic device simulators, computer-based simulations and head-mounted displays (HMDs). The haptic simulators were the most often used, whereas the HMD devices were the least-used technology in the field of healthcare. In immersive virtual environments, UX includes ten components. Most of the components were observed in the context of haptic devices and HMD devices, with all ten components being observed with the HMD devices. Almost all of the components were rated as positive. In conclusion, the development of VR technology has enabled the creation of the most comprehensive UXs, thus enhancing skill development, enabling remote access to training and, ultimately, improving patient safety. This review is important as it highlights the need for far more UX research within immersive virtual environments.